Impact of Drought on Poverty in Somalia - Pape, Utz; Wollburg, Philip (World Bank, Washington, DC, 2019)
Understanding the magnitude and importance of income shocks, such as drought or conflict, in causing and perpetuating poverty is critical to designing policies aimed at building resilience and contributing toward the goal of ending poverty. This paper uses micro-data from two waves of the Somali High Frequency Survey to assess the impact of the severe drought that Somalia experienced in 2016/17 on poverty, hunger, and consumption. The analysis uses a regression framework to quantify the effects of the drought, relying on spatial variation in drought exposure and the timing of data collection, which took place before and during the drought, for identification. The drought is found to have a sizable effect on poverty, consumption, and hunger in rural areas, where agricultural households and those lacking access to infrastructure and basic services are most severely affected. A renewed drought shock could lead to an increase in poverty of 9 percentage points. The findings underscore the importance of investing in rural resilience, especially among agricultural households.